Assessing farmers’ perception for resilience of socio-ecological production landscapes in central and eastern Kenya - Morimoto, Y.; Maundu, P.; Mijatović, Dunja; Bergamini, N.; Eyzaguirre, Pablo B. (United Nations University, 2015)
In order to understand farmers’ perceptions of resilience in socio-ecological production landscapes and seascapes (SEPLS), a participatory field assessment was conducted in Kenya. A tool developed by the United Nations University- Institute of Advanced Studies and Bioversity International was used to elucidate the range of perceptions of risk faced by five communities living in different agro-ecological and socio-economic conditions. This paper presents the practical process of carrying out assessments at the community level and also lessons learned while testing the toolkit. The process of using SEPLS indicators was confirmed valuable in: 1) identifying local perceptions of threats in landscape resilience, the perception differences in various community landscapes, major causes of threats and community efforts toward mitigation, 2) improving awareness through stimulating discussions with participants, and 3) providing a perspective on future directions and encouraging local innovations and potential interventions in response to negative trends. The discussions were considered vital in creating social capital for landscape governance, community ownership of the process and identifying potential interventions. A few areas of the tool were found wanting and some amendments have been advanced for consideration.